River Meanders, Tributary Junctions, and Antecedent Morphology - Jonathan D. Phillips (Hydrology)
Tributaries to meandering rivers rarely join the river on the interior of bends. The limited drainage area on bend interiors explains why tributaries seldom form there, but not why existing tributaries are redirected as meanders develop. Other relevant factors include flow dynamics at junctions, runoff partitioning on inner vs. outer bends, and tributary deflection as the main channel migrates laterally. This study investigated whether the lack of confluences on bend interiors applies to lower coastal plain rivers in South and North Carolina, USA, where the factors above are not necessarily active, and if so how tributaries at sites of developing meanders are redirected. Of the 121 confluences examined using GIS data supplemented with field observations, none occurred on meander bend interiors. A total of 17 cases of potentially deflected tributaries were identified. Of these, 11 had sufficient evidence for a confident interpretation of how redirection occurred. In all 11 cases, pre-bend river paleochannels were involved in redirecting the tributaries away from the bend interior. This is explained by a model showing that the local slope gradient and mean depth advantages of the paleochannels provide velocity, stream power, and shear stress advantages over extension of the tributary channel into the bend interior. The results illustrate the importance of local hydraulic selection, and the influence of antecedent morphology on river hydrology and geomorphology.